2021
DOI: 10.24093/awej/covid.1
|View full text |Cite
|
Sign up to set email alerts
|

English K-12 Teacher Experiences in Saudi Arabia in the Pandemic Era: A Follow-up Study of One Khbrat University Program

Abstract: A mixed-methods study examines the impact of the pandemic-driven move to virtual learning on K-12 (kindergarten through twelfth grade) English teacher experiences in Saudi Arabia to inform future development of the teaching of English in the country. Research is limited in K-12 English instruction in the country, and it is just emerging on the pandemic’s impact on education in the MENA region. The 35 subjects were English educators who completed the Saudi government-sponsored professional development program, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Or else, boredom, fatigue, and stress reduce the effectiveness. The challenges of online teaching presented by Daraghmeh et al (2021), Al-Samiri (2021) and are similar to the present study. As the social work education faculty of Australia felt, the faculty working in KSA also felt that there are issues with course delivery and active engagement of students.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Or else, boredom, fatigue, and stress reduce the effectiveness. The challenges of online teaching presented by Daraghmeh et al (2021), Al-Samiri (2021) and are similar to the present study. As the social work education faculty of Australia felt, the faculty working in KSA also felt that there are issues with course delivery and active engagement of students.…”
Section: Discussionsupporting
confidence: 89%
“…There were also some positive outcomes like flexibility of place and time. Daraghmeh, Mead, and Copeland (2021) examined the impact of the pandemic in K-12 English instruction in the MENA region of Saudi Arabia. The study explored technological, institutional and socio-cultural factors faced by Khbrat English teacher graduates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, online learning has yielded negative results for the teachers, students, and parents who have all experienced sudden unpreparedness in using online technologies, which is a matter that impeded effective learning worldwide (Al Salman et al, 2021). Furthermore, Daraghmeh et al (2021) found the need to leverage virtual technology and acquired knowledge and skills of Khbrat English teacher graduates to deliver EFL professional development with a more pedagogical focus and to build coalitions among EFL educators to sustain the forward movement of innovation in English education in post-pandemic Saudi Arabia.…”
Section: Difficulties In Online Language Learning and Teachingmentioning
confidence: 99%
“…Arab World English Journal www.awej.org ISSN: 2229-9327 81 To start with, Daraghmeh et al (2021) aimed to examine the effect of the shift to virtual learning in Saudi Arabia during the COVID-19 pandemic on the experiences of 35 English teachers who completed a professional development program at one U.S. university. Results showed different ways to empower virtual technology and acquired knowledge and skills of English teacher graduates to deliver EFL professional development with a more pedagogical focus and to build a kind of partnership and cooperation among EFL educators in Saudi Arabia.…”
Section: Literature Reviewmentioning
confidence: 99%